Review of Arbitration Practices in Construction Projects: A Case Study of Highway Projects in Nepal - Paudel, Chhabi Lal (Journal on Transportation System and Engineering, 2025)
Arbitration is a commonly adopted method for resolving disputes in construction contracts. The arbitration process and dispute settlement mechanisms are governed by legal provisions, contractual agreements between the parties, and procedures established by international institutions. However, in Nepal’s highway projects, the dispute resolution process has proven to be inefficient, adversely affecting contract management and overall project governance. To address this issue, this research examines existing arbitration practices, claim issues, and decision-making approaches using data and arbitration decisions from highway projects implemented under the Department of Roads. The study analyses 93 ongoing and completed arbitration cases to identify prevailing trends through qualitative and descriptive statistical analysis and investigates five detailed case study projects to explore current practices, issues, contractual and legal grounds for decision-making, and the effectiveness of dispute resolution in highway construction. The case studies are thoroughly reviewed using existing documentation available within the Department of Roads, providing valuable insights for project managers, planners, and contract administrators in identifying key dispute areas and arbitration decision approaches. Furthermore, this research contributes to understanding the trends, issues, and decision patterns in contractual claim resolution. Its findings support improvements in construction contract management by highlighting critical dispute areas that can be mitigated through proactive planning, effective arbitration handling, using standardised forms of contracts and capacity enhancement of stakeholders involved in resolving construction disputes.